2022
DOI: 10.3389/fnins.2022.855868
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging Changes in Patients Recovered From COVID-19: A Narrative Review

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused several outbreaks of highly contagious respiratory diseases worldwide. The respiratory symptoms of Coronavirus Disease-19 (COVID-19) have been closely monitored and studied, while the central nervous system (CNS) and peripheral system (PNS) lesions induced by COVID-19 have not received much attention. Currently, patients with COVID-19-associated encephalopathy present with dizziness, headache, anxiety and depression, stroke, epileptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…The pathophysiology of fatigue in PCS is still poorly understood. According to the first studies showing neuroimaging alterations in several brain regions [15][16][17][18], fatigue may involve a central mechanism. In this regard, impairment of GABAB-ergic neurotransmission has been detected using transcranial magnetic stimulation of the motor cortex [19,20], and another study found an association between APOE4 and post-COVID fatigue [21].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of fatigue in PCS is still poorly understood. According to the first studies showing neuroimaging alterations in several brain regions [15][16][17][18], fatigue may involve a central mechanism. In this regard, impairment of GABAB-ergic neurotransmission has been detected using transcranial magnetic stimulation of the motor cortex [19,20], and another study found an association between APOE4 and post-COVID fatigue [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have assessed structural damage to the central nervous system (CNS) using advanced MRI techniques, such as diffusion tensor imaging (DTI) in PwMS and failed to find a significant association between perceived fatigability and structural alterations (Codella et al 2002a , 2002b ). Similarly, recent studies in people with post-COVID-19 symptoms found no significant differences in MRI findings between subjects with and without cognitive impairments and fatigue after acute infection (Hellgren et al 2021 ; Huang et al 2022 ). Moreover, despite several studies detecting changes in brain microstructure of people with post-COVID-19 with structural MRI (Colonna et al 2020 ; Freeman et al 2021 ; Hixon et al 2021 ; Nuzzo et al 2021 ; Cecchini et al 2022 ) and DTI (Liu et al 2019 ; Tian et al 2020 ; Qin et al 2021 ), no correlations with fatigue symptoms have been reported.…”
Section: Discussionmentioning
confidence: 85%
“…Our results support the proposed correlation between brain hypometabolism and lasting cognitive deficits in COVID-19 patients one year after the infection. We found a heterogeneous pattern of abnormalities variably affecting prefrontal, temporal-mesial, parietal and pontine areas, those more affected during SARS-CoV-2 [ 27 29 ] infection. However, in our sample not all patients who had cognitive deficits showed hypometabolism as measured by FDG-PET.…”
Section: Discussionmentioning
confidence: 94%